Status of cyclone shelter facilities in south central Bangladesh - Amin, MN; Shil, SC; Hasan, M (Journal of Environmental Science and Natural Resources, 2016)
The south central region of Bangladesh is vulnerable to devastating cyclone. One of the most recognizable strategies to reduce risk of cyclone is cyclone shelter (CS). This study focuses on peoples perception on the status of cyclone shelter facilities in terms of its feasibility, water supply-sanitation facility and peoples expectation about overall environmental conditions etc. To review the perceived status of CS in south central region, a face to face questionnaire survey was conducted. Besides some key informants interview was also performed to validate the collected data by interview. The results revealed that the facilities of the CS were not satisfactory according to the most of the respondents. Among the respondents about 60% are highly vulnerable to cyclone. However, about 56% people were not interested to go CS during the disaster warning period because of the absence of connecting road. Another important issue that people indicated for going to CS was women security. More than 50% of the respondent perceived about unhealthy sanitation facilities. Safe drinking water, men and women separate bathroom perceived to be the important considerable factors among the CS facilities in the study area. J. Environ. Sci. & Natural Resources, 9(1): 75-79 2016